Unlocking the potential of immunotherapy for patients with resectable non–small cell lung cancer - Patel, Sandip Pravin; Gainor, Justin; Kao, Steven; Lee, Se-Hoon; Mok, Tony; Shah, Riyaz; Zhou, Caicun; Peters, Solange (Frontiers in Oncology, 2026)
Following positive results in advanced and metastatic non–small cell lung cancer (NSCLC), there has been a move toward the application of immunotherapy in the treatment of locally advanced, resectable, oncogene driver–negative disease. To date, there have been eight Phase III trials across the adjuvant, neoadjuvant, and perioperative settings that demonstrate benefit with (chemo)-immunotherapy in patients with resectable NSCLC. Given the wealth of immunotherapy treatment regimens both available and under investigation in this setting, there is a need to determine the optimal timing of immunotherapy treatment (neoadjuvant, perioperative, or adjuvant) across disease stages to aid clinical decision-making. Established treatment guidelines often diverge, highlighting the need for a multidisciplinary team approach and consensus decision-making based on the latest evidence in the resectable setting. Finally, there is an unmet need surrounding the role of key predictive factors and response assessments, to assist clinicians in selecting patients for immunotherapy regimens. The aim of this review is to evaluate the current data and key considerations surrounding immunotherapy for the treatment of resectable NSCLC, including key parameters to inform de-escalating and escalating treatment approaches.